Performance of handover procedure for enhanced relay LTE networks / Saliza Ramli - Ramli, Saliza (2013)
Over the next few years, billions of devices will be connected to the Internet creating tremendous demand for mobile wireless capacity and ubiquitous coverage. For most of these applications mobile users desire that their connections are maintained as their devices move from one access point to another to keep up with user preference. Long Term Evolution (LTE) networks provide the best solution for providing good services, larger bandwidth and larger coverage area. But due to overload condition of higher loaded cell that is alleviated by changing the adjacent cell reselection, relaying is needed in order to extend the coverage around cell edges and high shadowing environments and increasing the capacity in hot spot. This research focuses on mobility management in relay enhanced LTE networks by using MATLAB software. The results show that the effect of attaching relay in LTE networks has improved the performance of handover and transmission power.